Functional morphology of the taste buds of Florida manatee, Trichechus manatus latirostris - Barboza, Meghan L. B.; Larkin, Iskande L.V. (Marine Mammal Science, 2020)
The Florida manatee, Trichechus manatus latirostris, is a fully aquatic, threatened marine mammal for which increased understanding of their physiology, reproduction, and nutrition supports management decisions. Manatees may use taste to distinguish saltwater gradients, toxin detection, food assessment, and social interactions. This study sought to locate and characterize manatee taste buds comparing location, structure, number, and size to other species. Entire heads from manatees (6 males, 4 females) of various ages were obtained. The muzzle, tissue surrounding the nares, oral cavity, and epiglottis were examined grossly for pits and papillae. Tissues were examined using light and transmission electron microscopy. Within the predominant taste bud location, the tongue root, taste bud number was estimated using samples from four animals. The average number of taste buds within the tongue root was 11,534 (range 2,711–23,237) with sparse taste buds located on the soft palate and epiglottis. The location along the lateral surface of the tongue root and bordered by grooves, through which tastants could be easily transported, has functional significance. Large numbers of taste buds within the tongue root suggest that taste is an important component of manatee sensory systems and behavioral research would clarify this. © 2020 Society for Marine Mammalogy
6 citations (Crossref) [2023-10-31] tex.ids: barbozaFunctionalMorphologyTaste2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85083671006 type: Article
Keywords: Animalia; Florida [United States]; Mammalia; Trichechidae; Trichechus manatus; Trichechus manatus latirostris; chemoreception; dept.bio; detection method; functional morphology; histology; manatee; marine mammal; peer-reviewed; sensory system; taste; taste bud; tongue